2023
DOI: 10.1007/s00535-023-01963-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term hepatocyte function and portal hypertension outcomes of sofosbuvir/velpatasvir for decompensated hepatitis C-related cirrhosis

Abstract: Background It is unclear whether hepatocyte function and/or portal hypertension improves if a sustained virologic response (SVR) is achieved with direct-acting antivirals in patients with decompensated hepatitis C-related cirrhosis. Methods We examined the safety and efficacy of a 12-week course of sofosbuvir/velpatasvir (SOF/VEL) in 20 patients with decompensated hepatitis C-related cirrhosis. We also investigated changes in the hepatocyte receptor index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This observation was consistent with previous observations by Atsukawa et al 14 and Sano et al 15 Kotani et al reported that the function of hepatocytes improved after achieving SVR in patients with decompensated cirrhosis using Tc-99m-galactosyl human serum albumin scintigraphy. 16 However, the liver function did not improve in a half of the patients despite of achievement of SVR, and the reason for such phenomenon was uncertain. Thus, in the present study, we evaluated liver function as well as portal hypertension-related…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was consistent with previous observations by Atsukawa et al 14 and Sano et al 15 Kotani et al reported that the function of hepatocytes improved after achieving SVR in patients with decompensated cirrhosis using Tc-99m-galactosyl human serum albumin scintigraphy. 16 However, the liver function did not improve in a half of the patients despite of achievement of SVR, and the reason for such phenomenon was uncertain. Thus, in the present study, we evaluated liver function as well as portal hypertension-related…”
Section: Discussionmentioning
confidence: 99%
“…Kotani et al. reported that the function of hepatocytes improved after achieving SVR in patients with decompensated cirrhosis using Tc‐99m‐galactosyl human serum albumin scintigraphy 16 . However, the liver function did not improve in a half of the patients despite of achievement of SVR, and the reason for such phenomenon was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent report, DAA treatment of patients with hepatitis C-related decompensated cirrhosis improved the hepatic accumulation rate of Tc-99m-galactosyl human serum albumin and decreased the percentage of patients with severe portal hypertension (i.e., HVPG ≥12 mm Hg) from 92% to 58%; however, the HVPG did not decrease in patients with large splenic volume. 132 Therefore, in patients with hepatitis C-related cirrhosis and achieve SVR, HVPG decreases in the short term, but CSPH persists in many patients.…”
Section: Current Status and Future Prospects For Portal Hypertension ...mentioning
confidence: 99%